Do outro lado da tela: do consumo de telenovelas à subjetividade periférica das mulheres em Araguaína –TO. Uma discussão sobre recepção e interseccionalidade - Oliveira, Ana Rosa Carvalho de (2020)
The reception process involves who and how television arewatched, the understanding of television content will be mediated from the social place in which one is. In this sense, the trajectories and social experiences are buildingfrom this complex component, which will give rise to the constitution of subjectivity. In the light of feminist ethnography, we follow the process of receiving soap operas with women, collaborators of this research, as peripheral subjects, highlighting the gender and race constructions that cross them. Understanding that the subjectivities built fromthe periphery permeate their identities, the intersectionality of gender and race mark these subjects, in their subjectivities and in the formation of inequalities present in society. Thus, we build our narrative from everyday observing the discursive processes, and how it is perceived and received having mediation as a crossing in the language process until acquiring meaning and meaning.